2022
DOI: 10.3390/healthcare10061046
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Relationship between the BMI and the Sequence and Chronology of Eruption in Permanent Dentition in Spanish Population

Abstract: The aim was to analyze the relationship between BMI (body mass index) and the sequence and chronology of the eruption of permanent teeth in a sample of Spanish children. Methods: The study design was descriptive, cross-sectional, observational, and epidemiological. Patients of pediatric age were included. Emerged teeth, and patient’s age, race, and sex were recorded. The nutritional status of the child was assessed by calculating the BMI, according to the WHO parameters. Statistical analysis was carried out wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Also, in a recent study on a population of 725 pediatric patients aged between 4 and 14, no alterations to the eruption sequence of permanent teeth, nor influence on the teeth present was found. In this study the researchers concluded that bodyweight, height, age, and BMI act as significant predictors of dental eruption symmetry [20]. It is well known that factors such as deficient mastication, diet, and hormonal factors, among others, influence dental eruption; the correlation of said factors to dental eruption is yet to be determined.…”
Section: Discussionmentioning
confidence: 86%
“…Also, in a recent study on a population of 725 pediatric patients aged between 4 and 14, no alterations to the eruption sequence of permanent teeth, nor influence on the teeth present was found. In this study the researchers concluded that bodyweight, height, age, and BMI act as significant predictors of dental eruption symmetry [20]. It is well known that factors such as deficient mastication, diet, and hormonal factors, among others, influence dental eruption; the correlation of said factors to dental eruption is yet to be determined.…”
Section: Discussionmentioning
confidence: 86%
“…The same correlation was not found when permanent mandibular molars were considered. In the same way, Paz-Cortez 2022 showed that BMI category did not influence tooth eruption among children betweem 4 and 14 years of age ( 15 ).…”
Section: Discussionmentioning
confidence: 88%
“…After the cited systematic review, other studies were published with conflicting results. While some authors found that increased body weight was associated with early tooth eruption and advanced dental age ( 11 - 14 ), others revealed contradictory evidence, such as lack of association ( 15 ) or an inverted relationship ( 16 ). Paz-Cortez, 2022 when evaluating a sample of patients between 4-14 years old, showed that body mass index (BMI) did not influence tooth eruption ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation